New Paradigm of Complete Revascularization in Acute Coronary Syndrome with Multivessel Coronary Artery Disease: Is it Reasonable in Clinical Practice? - Adhika Prastya Wikananda; Mohammad Saifur Rohman; Novi Kurnianingsih; Cholid Tri Tjahjono (Heart Science Journal, 2021)
Coronary artery disease is the leading cause of illness and death in older adults. Around 40% to 50% of patients with ST-segment elevation myocardial infarction (STEMI) have multiple coronary artery disease. Multiple vessel coronary disease has been shown to improve cardiac outcomes and survival in patients who have undergone complete revascularization (CR) versus patients who have undergone only incomplete revascularization (ICR). When coronary angiography and PCI of the source of the infarction are performed on patients with STEMI, the risk of adverse cardiac death or myocardial infarction is significantly reduced. Additional research is needed to determine the efficacy of PCI of non-critical lesions. However, following procedures such as CABG or PCI, these procedures may be impossible to perform due to a variety of personal, anatomical, technical, and logistical barriers. In this review, we discussed about benefit of complete revascularization in patient acute coronary syndrome (ACS) with multivessel disease and which patient can be performed aggressive revascularization to achieved CR in clinical practice.Keywords: complete revascularization, acute coronary syndrome, percutaneous coronary intervention